(untitled) (Revista Ciência Agronômica, 2023)
The aim of this study was to evaluate the effect of salt stress and silicon fertiliser on growth and nutritional value in Brachiaria brizantha ‘MG5’. The experimental design was completely randomised in a 4 x 5 x 3 factorial scheme with four replications; the treatments consisted of four concentrations of sodium chloride (0, 20, 40 and 60 mmol L-1), with five concentrations of silicon (0, 1, 2, 3 and 4 mmol L-1) in the nutrient solution, and three cutting periods (30, 60 and 90 days). The concentration of 4 mmol L-1 silicon minimised the detrimental effects of the sodium chloride on regrowth. However, the levels of silicon application were not sufficient to reduce the harmful effects of the sodium chloride on nutritional value or on dry-matter production in Brachiaria brizantha ‘MG5’.